Análise dos parâmetros morfométricos da bacia do Rio Preto, Serra do Espinhaço (Minas Gerais, Brasil) - Lima, Camila de Sousa; Corrêa, Antonio Carlos de Barros; Nascimento, Nádia Regina do [UNESP] (My University, 2011)
The Rio Preto Hydrographic Basin (RPHB) is located in the North-central portion of the state of Minas Gerais, Brazil, 30 km ENE of the city of Diamantina. The sources of the stream of that name are found in the Rio Preto State Park, which has an area of 10,755 hectares. The total area, perimeter, extension, and axial length of the RPHB, as well as other morphometric characteristics, with emphasis on shape indexes, were obtained with the help of the ArcGis 9.2 program. The cartographic data were taken from digitalized topographic charts in a scale of 1:100,000 of the Brazilian Geographical Institute (IBGE). The measured drainage area is of 389.3 km2 and the perimeter is 136.9 km. Due to structural influence, the shape of the RPHB is irrgular and elongated, with drainage developed in a dendritic and parallel pattern. Those characteristics were checked by means of the compaxity coefficient and the shape factor. The first one was estimated in 1.94, what implies that the basin is not subject to fast flooding in years with normal precipitation. The high degree of fluvial downcutting of the basin is confirmed by the fact that it is a 5th order basin, it presents a significant branching rate and a medium drainage density.

A Bacia Hidrográfica do Rio Preto (BHRP) está situada no centro-norte do Estado de Minas Gerais, 30 km ENE da cidade de Diamantina. A nascente do Rio Preto encontra-se no Parque Estadual do Rio Preto, que possui uma área de 10.755 hectares. A área, o perímetro, a extensão, o comprimento axial da BHRP e as outras características morfométricas, enfatizando os índices de forma, foram extraídas com o auxílio do ArcGis 9.2. Os dados cartográficos foram obtidos das cartas topográficas digitalizadas na escala de 1:100.000 do IBGE. A área de drenagem encontrada foi de 389,3 km2 e o perímetro foi de 136,9 km. Devido às influências estruturais a forma da bacia do Rio Preto é alongada e irregular, com drenagem em padrão dendrítico e paralelo. Essas características foram comprovadas através do coeficiente de compacidade e fator de forma. O primeiro foi estimado em 1,94, o que implica que a bacia não é sujeita a enchentes em anos normais de precipitação. O alto grau de dissecação fluvial da bacia é confirmado por esta ser de 5ª ordem, apresentar uma ramificação significativa e uma densidade de drenagem média.
Analysis of the morphometric parameters of the rio preto basin, serra do espinhaço (minas gerais, Brazil)
Keywords: Brazil; Minas gerais; Morphometry; Morphostructural analysis; RDE index; Serra do espinhaço; cartography; flooding; GIS; morphometry; morphostructure; topographic mapping; Minas Gerais; Rio Preto State Park; Serra do Espinhaco